(untitled) (Eduscotech, 2023)
Social media has become an important platform for companies to connect with their target audience and make an impression. With the emergence of digital platforms, advertising effectiveness has become essential for marketers to determine the most efficient and appropriate communication media to place their advertisements. In this study, the problem is how the influence of audio video quality and the content quality of Shopee advertising video material on the YouTube platform has on user loyalty. This research was carried out using multiple linear regression analysis techniques. The population used is Shopee application users who are domiciled in the Madiun area and its surroundings. The sample used was collected as many as 36 respondents who were willing to fill out statements as the data needed in this study. The results of the study stated that there was an influence from the audio-visual quality of the Shopee advertising video that was broadcast on Youtube social media on user loyalty, there was an influence from the quality of the material content on the Shopee advertising video that was broadcast on Youtube social media on user loyalty and there was a joint effect of audio quality visuals and quality of material content in Shopee advertising videos that are displayed on YouTube social media on user loyalty. Based on the conclusions conveyed, the suggestion that can be conveyed is that a massive advertising exposure strategy is needed to increase user loyalty, but must also be based on professional creation and display techniques